Pengaruh Komitmen Manajemen Terhadap Standar Operasional Prosedur, Budaya Kerja, Dan Kepatuhan Kerja - Ahmad Rifa'i; Rina Anindita (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the influence between management commitment, on standard operating procedures (SOPs), work culture, and work compliance in the oil and gas industry. The research method used is quantitative by collecting data from employees in various positions such as managers, supervisors, staff, technicians and operators in one of the oil and gas companies in the Bekasi area. The results of the study show that management commitment has a significant positive influence on the implementation of standard operating procedures, management commitment has a negative influence on the implementation of work compliance, management commitment has a significant positive influence on the implementation of work culture, standard operating procedures have a significant positive influence on the implementation of work culture, in addition to a strong work culture is proven to play an important role in improve employee work compliance in the oil and gas industry.